Relation between active mediation, exposure to Daniel Tiger's Neighborhood, and US preschoolers' social and emotional development. Issue 4 (1st October 2016) - Rasmussen, Eric E; Shafer, Autumn; Colwell, Malinda J.; White, Shawna; Punyanunt-Carter, Narissra; Densley, Rebecca L.; Wright, Holly
Abstract: This study explored the relationship between active mediation, exposure to Daniel Tiger's Neighborhood, and key indicators of preschoolers' social and emotional development. One hundred and twenty-seven children aged 2–6 either watched or did not watch 10 episodes of Daniel Tiger's Neighborhood over a two-week period. Results revealed that preschoolers who watched the program exhibited higher levels of empathy, self-efficacy, and emotion recognition when their regular TV-watching experiences are frequently accompanied by active mediation. This was especially true for younger preschoolers and preschoolers from low-income families. Implications for policy-makers, parents, producers of prosocial programming, and educators are discussed.